Cidadania autoconstruída: o ciclo de lutas sociais das ocupações urbanas na RMBH (2006 - 2015) - Rafael Reis Bittencourt (2016)
This study describes and analyses the historic cycle of urban occupations for the right to housing that is stabilished in Belo Horizonte and its metropolitan area, starting in 2006, marking a new context of ensurance of the right to the city that involves more than fifteen thousand families in twenty-five experiences. It is understood that this cycle is caracterized by a self-managed housing policy, that is, developed by social actors from the civil society, not only without the cooperation, but against the State, starting with the appropriation of empty properties (horizontal lands) held by land speculation (and not fulfilling their social function), being in this sense in open dispute with real state capital and the urban project that sustains it; with the process of housing units production parting from self-construction and sustaining its legitimacy by means of a social network of technical support based on solidarity and citizenship, whose centrality is occupied by the organized social movements. Moreover, limits and contradictions of these experiences are also discussed, regarding the guarantee of the right to housing and the fulfillment of a wide, structural and effective urban reform.